Praktik Pembukuan Pada PT. Pelita Susun Bentang Organik Tahun 2023 - Zubir; Candra Irawan; Menhard; Silvia Oktaviani; Robby Sandi (Journal of Creative Power and Ambition (JCPA), 2024)
MSMEs play an important role in economic growth. There are several problems faced by MSMEs at this time including difficulties in marketing, limited innovation and technology, as well as limited knowledge about make financial statements. In order to increase interest in the importance of knowledge about financial statements, This community service activities are very necessary at this time. The method of devotion is done by giving Lectures, Discussions and Mentoring. The results of this activity, MSME actors already understand how to make financial statements, namely balance sheets and income statements